Development of Immunotherapy Strategies Targeting Tumor Microenvironment Is Fiercely Ongoing - Bai, Rilan; Cui, Jiuwei (Frontiers in Immunology, 2022)
Tumor immune microenvironment is a very complex system that is influenced by a wide range of factors; in this microenvironment, various immune cells, stromal cells, and cytokines can interact with tumor cells and jointly regulate this complex ecosystem. During tumor development, the tumor microenvironment (TME) shows the upregulation of inhibitory signals and downregulation of activating signals, which result in an immunosuppressive microenvironment and lead to tumor immune escape. In recent years, a variety of precision immunotherapy strategies have been developed to remodel the TME into a positive immune microenvironment by stimulating or restoring the inherent tumor inhibition ability of the immune system so as to improve anti-tumor therapeutic efficacy. This review focuses on immunotherapy strategies targeting the TME, including those that target the microenvironment to inhibit signaling, activate signaling, and specifically involve many new targets such as physical barriers, immune cells and their surface molecular receptors, cytokines, and metabolic factors. Furthermore, it summarizes the challenges faced while conducting research on the tumor immune microenvironment and the corresponding solutions.